BEBERAPA SIFAT PEMETAAN C-KONTRAKTIF DI RUANG METRIK PARSIAL DAN TITIK TETAPNYA - WAHIDATUSSOLIHAH, ROSANTI; AINI, QURRATUL; MARWAN, MARWAN (E-Jurnal Matematika; Vol 14 No 1 (2025)DO - 10.24843/MTK.2025.v14.i01.p472, 2025)
Partial metric space is a generalization of ordinary metric space, in partial metric space the axiom d(x,x) is no longer necessarily zero. Partial metric space was first introduced in 1994, since then many researchers have continued to learn about partial metric spaces. Fixed point is one of the interesting topic to learn in partial metric spaces, so many researchers have conducted research on this topic.. In this research, the researcher study the concept of C-contractive mapping in partial metric space and the existence of fixed point from this mapping. This research was conducted using a literature review, by collecting scientific articles and books related to the topic of this research. The results show that if  is a mapping in complete partial metric space that satisfies the condition  with  then  has fixed point